Pelatihan Metode Pembelajaran Menyenangkan Berbasis Integrated Joyful Religious Learning - Salahuddin; MS, Uyun Nafiah; Sakunti, Sri Ramdayeni; Safitri, Resdiana; Fikri, Ahmad; M. Yahuda; Hasirah (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Islamic religious education at primary madrasahs plays a pivotal role in moulding the moral and spiritual values of the youth. This article introduces a specialized training program for primary madrasah educators known as the "Integrated Joyful Religious Learning Method." The purpose of this training is to incorporate elements of joy into the teaching of Islamic religious values, creating a dynamic learning environment and deepening students' comprehension of these teachings. Unlike typical instructional sessions, this training actively engages teachers in the development and application of this method in their teaching practices. The outcomes of this training have demonstrated enhanced teaching skills among educators, increased student enthusiasm for learning, and a more profound grasp of Islamic principles. The article also suggests several steps for further improvement in Islamic religious education at primary madrasahs, including periodic assessments, the creation of teaching materials, information dissemination, and ongoing support. This training program holds significant potential for elevating the quality of Islamic religious education and empowering teachers to effectively shape the younger generation's education.